Developing product label information to support evidence-informed use of vaccines in pregnancy. Issue 48 (15th November 2019) - Manca, Terra A.; Graham, Janice E.; Dubé, Ève; Kervin, Melissa; Castillo, Eliana; Crowcroft, Natasha S.; Fell, Deshayne B.; Hadskis, Michael; Mannerfeldt, Jaelene M.; Greyson, Devon; MacDonald, Noni E.; Top, Karina A.; et al.
Highlights: Consensus-based methods were used to improve vaccine product label information. Stakeholders developed structure, language, and content for product labels. Emergent methods exposed divergent understandings of the purpose of product labels. Stakeholders were concerned about how product labels are regulated. Developers of product label information should consider involving end users. Abstract: Background: Product labelling information describing the use of vaccines in pregnancy continues to contain cautionary language even after clinical and epidemiological evidence of safety becomes available. This language raises safety concerns among healthcare providers who may hesitate to recommend vaccines during pregnancy. Purpose: To develop clear evidence-based language about vaccine safety and effectiveness in pregnancy for inclusion in vaccine product labels. Methods: We conducted a three-stage consensus-methods project with stakeholders, including: healthcare providers, vaccine regulators, industry representatives, and experts in public health, communication, law, ethics, and social sciences. Using qualitative and quantitative methods, we held a nominal group technique (NGT) meeting, followed by a Delphi survey, and then a consensus workshop with a subset of Delphi participants. We developed a methodological tool to analyse data for consensus. Principal results: Stakeholders (N = 14) at the NGT meeting drafted product label statements for evaluation in the Delphi survey. Survey participants (N = 41) provided feedback on statements for five hypothetical vaccines. Workshop participants (N = 27) initiated discussions that demonstrated a lack of awareness that the regulatory purpose of product labels is to provide a scientific summary of product-specific pre-clinical and clinical trial data. Each stage of this project built on earlier stages until we achieved strong consensus on the language, structure, and types of data that stakeholders wanted to include in inactivated influenza vaccine (IIV) and tetanus-diphtheria-acellular pertussis (Tdap) vaccine product labels in Canada. Conclusions: The revised statements for IIV and Tdap aligned with workshop participants' goals that the product label be evidence-based, with a consistent structure and language that is easily understood by healthcare providers. Emergent methods uncovered stakeholder concerns about the regulatory purpose, content, and evidence used in product labels. Involving healthcare providers in the development and regular updating of product information could prevent interpretations of that information that contribute to vaccine hesitancy.